Quantification of small extracellular vesicles by size exclusion chromatography with fluorescence detection - Xu, Rui (Anal Chem, 2016)
Chemical analysis of small extracellular vesicles (sEVs) circulating in body fluids holds potentials in non-invasive diagnosis of diseases and evaluation of therapeutic treatments. However, quantification of sEVs remains a challenge due to lacking of cost-effective analytical protocols. Herein we report a facile method based on size exclusion chromatography with fluorescence detection (SEC-FD) for sEVs quantification. After removal of cells and cell debris, a 0.50-mL sample (e.g. cell culture medium) is incubated with CM-Dil dye to fluorescently label sEVs. The incubation solution is then separated on a SEC column packed with Sepharose CL-4B. The eluent is monitored fluorescently at Ex553nm/Em570nm by using a fluorometer equipped with a 50-μL flow through cuvette. Separation efficiency of the proposed SEC-FD method was evaluated by analyzing 100-nm liposomes and albumin-FITC conjugate. Liposomes were eluted out in less than 6 min, about 10 min before albumin-FITC. A separation repeatability (RSD in retention time) of 1.4% (n=5) was obtained for liposomes. In analysis of cell culture media, linear calibration curves based on SEC-FD peak height versus sEVs concentration were obtained with r(2) value of 0.996. Intra-day quantification repeatability (RSD in peak height) was 3.2% (n=5). Detection limitwas estimated to be 2.9 × 10(7) exosome particles/mL. The proposed assay was applied to the first study of sEVs secretion from TK6 cells cultured in serum-free medium for a culturing period from 1 to 48 hours.